Blagotvoritel'nyi detskii dom po zashchite detei invalidov i sirot . Blagotvoritel'nyi detskii dom po zashchite detei invalidov i sirot . Charity Organization for the Protection of Disabled Children and Orphans . Благотворительный детский дом по защите детей инвалидов и сирот - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program about compassion. Featured in the program: Livitskaia, Marichika Petrovna (Director of the Foundation "Marichika") Программа о сострадании. В программе участвуют: Ливицкая, Маричика Петровна (Директор фонда "Маричика")